(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
In Bali, architecture was regarded as undergoing minimal alteration. However, this article argues that architecture in Bali has never been a neutral carrier of culture. Instead, it is a place where colonial legacies, postcolonial nation-building, and global tourists all meet. The goal of this study is to track the emergence and development of contemporary architecture in Bali to understand the elements that impact its change. Historical approaches were applied to discover knowledge from the past by combining data from numerous sources. Archival study, building surveys, and stakeholder consultations are part of the research. The material was discussed using synchronic and diachronic analysis to produce a more in-depth study. Findings reveal that different governments’ political and economic growth tactics contributed significantly to the alteration of Bali’s architecture. The colony’s exposure to the international world in the beginning of the twentieth century influenced investment in Bali. On one hand, the economic boom encouraged modern architecture. On the other, new construction typologies, not always rooted in tradition, raised awareness that this sector needs regulation. This research demonstrated that architecture in Bali has undergone significant developments, particularly due to adaptation to new socio-cultural and economic transformations.